Manufacturing employment and exchange rates in the Portuguese economy: The role of openness, technology and labour market rigidity - Fernando Alexandre; Pedro Baç\~ao; Jo\~ao Cerejeira; Miguel Portela (Institute for the Study of Labor (IZA), 2010)
In this paper, we explore empirically the role of openness, technology and labour market rigidity in the determination of the effect of the exchange rate on employment in Portugal. We develop an index that allows us to measure labour market flexibility at the sector level. This index shows that labour market flexibility has been increasing in all manufacturing sectors and that the labour market in high technology sectors is more flexible than in low technology sectors. We use this index in the estimation of an employment regression, focusing on the effect of exchange rate movements. Our estimates indicate that employment in lowtechnology sectors, with a high degree of trade openness and facing less rigidity in the labour market are more sensitive to movements in exchange rates.
Keywords: J23; F16; F41; 330; exchange rates; international trade; job flows; labour market rigidity; technology